Highly stable low cost anode interfacial material preparation and characterization via hydrothermal route for organic solar cell. (2017) - Geetha, D.; Ramesh, P.S.
Abstract: One of the biggest challenges for mankind in this century is to secure a long term energy supply for sustainable global development. Traditional OSCs has PEDOT: PSS was anode interface layer (AIL). These PEDOT: PSS have acidic nature, which results in degradation mechanisms and reduces device stability. Hence a new material to enhance the stability and reduce the corrosiveness is needed. Also the material should posses (i) high optical transparency, good chemical stability, a large ionization potential and good electron blocking capacity. Here we demonstrate the availability of a well-established procedure for fabricating reliable and reproducible interfacial material for organic solar cells. Earth abundant, low cost and cheap copper sulfide (CuS) was chosen for the study. We present here a simple, cheap and fast method of preparation of CuS, also we reported the synthesis and formation mechanism of nano CuS by simple hydrothermal route at constant temperature 200°C. The concentration of stabilizing agent (surfactants) and the charge of surfactants play important role in determining the morphology and composition of the product. The surfactant is found to be important criteria for obtaining dispersed nanocrystals. The stability of CuS and the formation of different compounds are studied in detail using thermal analysis and X-ray diffraction (XRD). SEM and AFM images showed well defined hexagonal faced spherical nanoparticles of size 15 nm in three different surfactants stabilized CuS. The phase pure CuS is found to be completely get transformation to Cu2S and CuO at 700°C without any intermediate phases. The optical band gap of the synthesized CuS nanostructure is measured and mechanism behind this synthesis was discussed and reported.